2020
DOI: 10.3390/antibiotics9070369
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antifungal Activity of Rare Substituted 1,2,3-Thiaselenazoles and Corresponding Matched Pair 1,2,3-Dithiazoles

Abstract: We report our investigations into the underlying differences between 1,2,3-dithiazole and their ultra-rare counterpart, 1,2,3-thiaselenazole. This rare 1,2,3-thiaselenazole chemotype was afforded by sulfur extrusion and selenium insertion into the preconstructed 1,2,3-dithiazoles. We built a library of matched paired compounds to compare and contrast the two ring systems. This led to the development of both narrow and broad-spectrum antimicrobial compounds with sub-micro molar potency, limited to no to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…[2,3] In this context, the unique properties of organoselenium compounds which efficiently scavenge and induce reactive oxygen species has led to a renewed interest in their application across medicinal chemistry, including use as antifungals and antibacterials. [4][5][6][7][8][9][10] The chemistry of imidazo [4,5-d]imidazol-2,5(1H,3H)-diones (glycolurils) and their analogs is our area of interest. [11][12][13] We are developing methods for the synthesis of glycolurils I, [11,12] their 5-thioxo II, [11,12] 5-imino III [12] derivatives and 3thioxoperhydroimidazo[4,5-e]-1,2,4-triazin-2-ones IV (3-thioxoimidazotriazin-2-ones) [11] and studying their properties (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] In this context, the unique properties of organoselenium compounds which efficiently scavenge and induce reactive oxygen species has led to a renewed interest in their application across medicinal chemistry, including use as antifungals and antibacterials. [4][5][6][7][8][9][10] The chemistry of imidazo [4,5-d]imidazol-2,5(1H,3H)-diones (glycolurils) and their analogs is our area of interest. [11][12][13] We are developing methods for the synthesis of glycolurils I, [11,12] their 5-thioxo II, [11,12] 5-imino III [12] derivatives and 3thioxoperhydroimidazo[4,5-e]-1,2,4-triazin-2-ones IV (3-thioxoimidazotriazin-2-ones) [11] and studying their properties (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that selenium compounds such as thiaselenazoles, dithiazoles, and selenium–platinum complexes are effective antimicrobial and antiviral agents [ 9 , 10 , 11 , 12 , 13 ]. These agents allow for both narrow- and broad-spectrum antimicrobial and viral activity at micromolar concentrations with limited toxicity [ 9 , 10 , 11 , 12 , 13 ]. Furthermore, these agents are effective against multidrug-resistant bacteria and the formation of bacterial biofilms [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These agents allow for both narrow- and broad-spectrum antimicrobial and viral activity at micromolar concentrations with limited toxicity [ 9 , 10 , 11 , 12 , 13 ]. Furthermore, these agents are effective against multidrug-resistant bacteria and the formation of bacterial biofilms [ 9 , 10 , 11 , 12 , 13 ]. An ideal antibacterial drug would target the virulence mechanisms of bacterial pathogens and not be affected by existing resistance mechanisms in these bacteria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5-Dichloro-1,2,3-dithiazolium chloride ( 1 ) (aka “Appel’s salt”), prepared from chloroacetonitrile and disulfur dichloride [ 1 , 2 ], is the main precursor to monocyclic 1,2,3-dithiazoles, and in particular 4-chloro-5 H -1,2,3-dithiazoles 2 ( Scheme 1 ) [ 3 , 4 , 5 , 6 ]. Several 5 H -1,2,3-dithiazoles display biological activities against bacteria [ 7 , 8 , 9 , 10 ], viruses [ 11 , 12 ], fungi/weeds [ 13 , 14 , 15 , 16 , 17 , 18 ] and cancers [ 19 , 20 , 21 ]. Furthermore, 4-chloro-5 H -1,2,3-dithiazoles 2 are useful intermediates in organic synthesis [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%